Critical Theory and the Concept of the Text in the Modern German Criticism (Journal of the College of Languages (JCL), 2014)
The identification of the thought and philosophy of the textual configuration in the modern German criticism leads us directly to contemplate the concept and identity of the text and the critical theory for the poles of Frankfort criticism school and its pioneers. This school (according to my assessment is the leading basis of the text theory of the ideological modern German criticism) has become the backbone of many critical theories, trends and writings of the post-modernism, particularly philosophy, sociology, psychology, anthropology, literature, criticism, criticism of criticism, fine arts, and music.